Treatment of periocular hyperpigmentation due to lead of kohl (surma) by penicillamine: A single group non-randomized clinical trial - El Safoury Omar; Abd El Fatah Dina; Ibrahim Magdy (Wolters Kluwer Medknow Publications, 2009)
Background: Periocular hyperpigmentation is a condition in which skin of eyelids become darker in color than the normal surrounding skin. Lead and other heavy metals produce increased pigmentation because of deposition of metal particles in the dermis and increased epidermal melanin production. Aims: This study was conducted to evaluate the dual effect of chelation therapy in treating periocular hyperpigmentation and lead toxicity. Methods: The study population consisted of nine females complaining from dark coloration of their eyelids. The nine females were continuously using kohl as eyeliner. Lead levels in conjunctiva and serum before and after D-penicillamine (D-PCN) oral administration were estimated in relation to vertical, horizontal length, and degree of hyperpigmentation score. Results: Highly significant P values (0.000) were obtained as regard to the conjunctival lead levels, serum lead levels, horizontal length, and degree of darkness score before and after D-PCN therapy. A less significant P value (0.040) was recorded as regard to the vertical length. Conclusion: Regardless other causes, this study spots the light on a new concept for periocular hyperpigmentation from lead toxicity in adult females using kohl and suggests D-PCN in a low divided dose (750 mg/day) for its treatment.